Influence of irrigation frequency and nitrogen concentration on Tifway 419 bermudagrass in Brazil - dos Santos, Patrick Luan Ferreira [UNESP]; do Nascimento, Matheus Vinícios Leal [UNESP]; de Godoy, Leandro José Grava [UNESP]; Zabotto, Alessandro Reinaldo [UNESP]; Tavares, Armando Reis; Bôas, Roberto Lyra Villas [UNESP] (FapUNIFESP (SciELO), 2022)
Tifway 419 Bermudagrass is widely used on athletic fields, requiring irrigation and fertilization for its maintenance; however, little information is available for Bermudagrass management in tropical countries, as Brazil. Thus, this study aimed to evaluate the effect of irrigation frequency and nitrogen (N) fertilization on the development of Tifway 419 Bermudagrass. The experiment was carried in 2019, applying two irrigation frequencies (daily and every two days) and five N concentrations of 0, 42.19, 63.28, 105.47 and 126.56 kg N ha-1 divided into three 30-day increments. Photosynthetic pigments, grass height, accumulated dry mass, relative chlorophyll index, regeneration rate, root length, and dry mass of root, rhizome and stolon were analyzed. The best result was observed in between 63.28 and 105.47 kg N ha-1 (15% N) and irrigated every two days. The treatment maintains the green color of the grass. Maximum Bermudagrass regeneration rate was observed within this interval, and the root length and dry mass of roots, rhizomes and stolons were higher compared to the highest concentration.
Keywords: Athletic fields; Cynodon spp.; Irrigation management.; Nitrogen fertilization